Intradermal and transdermal absorption of beta-naphthylamine and N-Phenyl-beta-naphthylamine in a viable human skin model - Mini Vijayan, Suvarna; Baierl, Moritz; Göen, Thomas; Horch, Raymund E.; Ludolph, Ingo; Drexler, Hans; Kilo, Sonja (Toxicology in Vitro, 2024)
Technical products containing N-Phenyl-beta-naphthylamine (PBNA) are contaminated with beta-naphthylamine (BNA), a known carcinogen. Both amines penetrate the skin to different degrees, but little is known about their dermal-depot formation. This study investigated the dermal penetration of PBNA and its degradation product BNA using a viable human-skin model. PBNA (259 μg) or BNA (0.52 μg) in n-hexane and industrial grease were applied to freshly excised human skin (n = 6, 0.64 cm2) for 2-72 h. After temporary/continuous and single/repeated exposure, samples were taken (stratum corneum, epidermis/dermis, receptor fluid) and analyzed for their amine content by GC–MS. Continuous exposure led to a PBNA dermal depot of ∼47 μg/cm2 over 72 h. Temporary applications also resulted in lower but consistent PBNA dermal depots. A single 2-h application resulted in a dermal depot of ∼16 μg/cm2 after 72 h, while this was ∼25 μg/0.64 cm2 with repeated applications. BNA behaved differently; with repeated 2-h applications, intradermally retained BNA initially increased 3–6 fold, then dropped to ∼200–250 ng/cm2. This incomplete decline upon repeated short-term exposure to PBNA suggests that a BNA dermal depot is formed either due to contamination of PBNA with BNA or to enzymatic conversion of PBNA to BNA. Additionally, PBNA dermal depots were saturable under the given conditions. These findings highlight the importance of understanding the dermal-exposure dynamics of potential carcinogenic compounds in industrial settings.
CRIS-Team Scopus Importer:2024-10-18
Keywords: beta-naphthylamine; Dermal depot; Intradermal penetration; N-Phenyl-beta-naphthylamine; Transdermal absorption; Viable skin